(untitled) (Acta Scientiarum. Health Sciences, 2020)
This study aimed to obtain personal and clinical characteristics of patients with fibromyalgia, and to identify the factors responsible for the initiation, recurrence or intensification of painful state in each patient. The information was collected using General Characterization Form of Fibromyalgia Patients, consisting of 32 questions about personal data, location, and type of pain, identification of factors or circumstances related to the algetic state, physical activity, and pharmacological treatment. Among 14 patients included in this study, 85.71% were female. The pain intensity and time spam varied among patients, and 42.85% of them presented pain (algetic state) lasting between 6 to 10 years. Emotional trauma was the factor or circumstance related to the onset of symptoms of 71.43% of the patients. All patients reported that stressful situations resulting from conflicts in the family, social or work environment are factors responsible for reactivating and intensifying the symptoms of fibromyalgia. Factors and circumstances related to the onset, recurrence, and intensity of fibromyalgia symptoms reveal that it is necessary to inform patients that it is a benign disease, despite the painful condition,since the way they respond to daily events is a determining factor in the course of the disease.Improving physical conditioning and conducting cognitive-behavioral therapy, along with pharmacological treatments, can be successful in treating or minimizing the symptoms of fibromyalgia.